ANALISIS PERBANDINGAN WAKTU DALAM ESTIMASI BIAYA PEKERJAAN STRUKTUR PROYEK GEDUNG PRESISI 5 POLRI: METODE KONVENSIONAL VS BIM 5D - Manurung, Edison Hatoguan; Hutagaol, Kerlima; Putrafakhmi, Dizzy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study compares the cost estimation time for structural work between conventional methods and 5D BIM for the Precision 5 National Police Building Project. Using a quantitative approach and case study, data was obtained from project documentation and simulations. The results show that 5D BIM significantly accelerated the estimation process without compromising accuracy.